P95 Exploring the timing of Hypertonic Saline (HTS) and Airways Clearance Techniques (ACT) in Cystic Fibrosis (CF): a cross over study. (15th November 2016) - O'Neill, K; Moran, F; Bradbury, I; Downey, DG; Rendall, J; Tunney, MM; Elborn, JS; Bradley, JM
Abstract : Background: Streamlining the timing of treatments in CF is important to optimise adherence whilst ensuring efficacy. The optimal timing of HTS and ACTs is unknown. Objectives: This study hypothesised that ACTs after HTS would be more effective than ACTs during HTS as measured by lung clearance index (LCI). FEV1, sputum weight and patient perceptions were also compared. Methods: Adults with CF providing written informed consent were randomised (between days 10–14 of intravenous antibiotic course during a pulmonary exacerbation) to a crossover trial of ACTs after HTS inhalation or ACTs during HTS inhalation on alternate days. ACT treatment consisted of 10 cycles of active cycle of breathing technique using an Acapella®. The physiotherapist collecting the outcome measures was blinded. Patients completed a Multiple Breath Washout (MBW) test to obtain LCI and spirometry at baseline and 90 mins post treatment. Sputum collection during 90 mins, ease of clearance and satisfaction with treatment was also recorded. Wilcoxon test was used and p < 0.05 was considered significant. Results: Fourteen subjects were recruited and 13 completed the study (mean [SD] age 33 [12], FEV1% predicted 51 [22], LCI (no. turnovers) 14 [4]). Comparing the 2 treatments (ACT after HTS vs ACT during HTS), the change from baseline to 90 mins post treatment in LCI (p = 0.71) and FEV1% predicted (p = 0.97) was not significant. There was also no difference in sputum weight expectorated (p = 0.17), patient perceived ease of clearance (p = 0.33) or satisfaction (p = 0.28). The time taken for ACT during HTS was significantly shorter (p = 0.001). Conclusions: In this small study, ACTs after HTS was no more effective than ACTs during HTS.